The classroom flow and engagement experiences of Western Australian rural and remote secondary school students - Cavanagh, Rob (Society for the Provision of Education for Rural Australia, 2014)
This paper commences with a brief examination of non-metropolitan student engagement and participation in schooling. It then describes how student engagement in classroom learning was conceptualised utilising Flow Theory. The key elements in this conception were subsequently used to construct an interview schedule. The characteristics of the sample of students interviewed are presented and then the data collection procedures are explained. The application of an inductive data analysis technique to these data is explicated. The empirical results are discussed in consideration of the extant literature on student engagement and flow. This study was part of a much larger mixed-methods investigation funded by the Australian Research Council from 2008 to 2011 and concluded in 2012. It was conducted in Western Australian public schools with the support of the, then, Department of Education and Training.